KEPERCAYAAN BUAYA GAIB DALAM PERSPEKTIF URANG BANJAR BATANG BANYU DI SUNGAI TABALONG - Mursalin Mursalin (JURNAL SOCIUS, 2015)
The background of this research is the beliefe in invisible crocodiles believed by Banjarese of Batang Banyu, in Tabalong River. People there, up to now stil have that kind of belief. The problem in this research si the perspectives Banjarese of Batang Banyu towards invisible crocodiles. The objective is to find out the beliefs Banjarese of Batang Banyu in Tabalong River associated with the invisible crocodiles. A belief which is manifested in an action called ritual. Method for this research was qualitative descriptive with ethnography approach. Before data were collected, first, formulation of the research, research objectives, and literature studies was done. Then, the data collection was carried out in triangulation: indirect observation, interviews and documentation stages. The result showed that belief in the invisible crocodiles caused by their river living environment. In the river, there are strong and ferocious crocodiles. The ability of this crocodiles then is feared and admired by Banjarese People of Batang Banyu. Th feelings of fear and admiration is expressed in a ritual of malabuh. Keyword: Belief, Invisible Crocodile, Banjarese People of Batang Banyu, Tabalong River.